2005
DOI: 10.1002/cne.20764
|View full text |Cite
|
Sign up to set email alerts
|

Projections from the subfornical region of the lateral hypothalamic area

Abstract: The L-shaped anterior zone of the lateral hypothalamic area's subfornical region (LHAsfa) is delineated by a pontine nucleus incertus input. Functional evidence suggests that the subfornical region and nucleus incertus modulate foraging and defensive behaviors, although subfornical region connections are poorly understood. A high-resolution Phaseolus vulgaris-leucoagglutinin (PHAL) structural analysis is presented here of the LHAsfa neuron population's overall axonal projection pattern. The strongest LHAsfa ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
93
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 63 publications
20
93
0
2
Order By: Relevance
“…39,40]. If we are to understand how ingestive behaviors are controlled, a major challenge is now to define the detailed connectional and functional architecture of this highly complex brain region and to determine whether any of these neurons receive convergent information from the different inputs that can control feeding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…39,40]. If we are to understand how ingestive behaviors are controlled, a major challenge is now to define the detailed connectional and functional architecture of this highly complex brain region and to determine whether any of these neurons receive convergent information from the different inputs that can control feeding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2, the dorsal PAG, in particular its dorsolateral part, provides massive ascending projections to the AHN and LHAsf, both of which are known to provide strong inputs into the dorsal premammillary nucleus (PMd; Goto et al, 2005;Risold et al, 1994), where marked activation has been reported in response to electrical stimulation aimed at the dorsal PAG (Vianna et al, 2003). Notably, the PMd appears to be a critical element in the ascending pathway involved in fear learning using dorsal PAG activation as the US, and PMd beta-adrenergic blockade has been shown to impair fear conditioning in a paradigm that associates neutral odor cues as the CS and chemical stimulation of dorsal PAG as the US (Kincheski et al, 2012).…”
Section: Pag and Fear Learningmentioning
confidence: 99%
“…Hypothalamic projections to the dlPAG arise primarily from the dorsal (DHA), posterior (PHA), and anterior (AHA) hypothalamic areas (particularly its lateral aspect; Semenenko and Lumb, 1992), as well as from the dorsomedial subdivision of ventromedial hypothalamic nucleus (VMHdm) (Veening et al, 1982(Veening et al, , 1987(Veening et al, , 1991Floyd et al, 2001). There is also a significant input to the dlPAG, from the dorsal premammillary nucleus of the hypothalamus, particularly its ventromedial portion (Goto et al, (2005).…”
Section: Forebrain Afferentsmentioning
confidence: 99%